Social participation patterns and the incidence of functional disability: The Japan Gerontological Evaluation Study. Issue 8 (30th June 2020) - Ukawa, Shigekazu; Tamakoshi, Akiko; Okada, Yutaka; Ito, Yoichi M; Taniguchi, Rika; Tani, Yukako; Sasaki, Yuri; Saito, Junko; Haseda, Maho; Kondo, Naoki; Kondo, Katsunori
Abstract : Aim: To examine whether patterns of social participation vary in their associations with functional disability. Methods: Data from 44 978 participants (22 750 men and 22 228 women) who participated in the 2010 Japan Gerontological Evaluation Study were analyzed; a study of those aged ≥65 years from 23 municipalities in eight prefectures. Social participation information was obtained at baseline with an eight‐item questionnaire. Incidence of functional disability from 2010 to 2013 was defined as a new certification of eligibility for municipal public long‐term care insurance. Social participation patterns were analyzed using exploratory factor analysis and participants were classified into quartiles of factor scores of social participation patterns. A competing risk model was used to calculate the hazard ratios and 95% confidence intervals for the incidence of functional disability in 3 years of follow‐up. Results: Two social patterns were identified: sports groups/clubs and hobby groups, and political groups/organizations and industry/trade associations. For both patterns, compared with participants in the lowest quartile, participants in the highest quartile were more likely to be male, college educated, high‐income and current drinkers. Both patterns were associated with reduced incidence of functional disability (adjusted hazard ratios for top quartile of sports and hobby pattern: 0.66, 95% confidence interval: 0.59, 0.74; for political and industry/trade pattern: 0.81, 95% confidence interval: 0.72, 0.90; P for trend <0.001 for both). Conclusions: Those whose social participation patterns were characterized by frequent participation in sports groups/clubs and hobby groups or political groups/organizations and industry/trade associations were less likely to develop a functional disability. Geriatr Gerontol Int 2020; 20: 765–772 .